Makna Ikonologi dan Ikonografi Pada Karya Mural Youngsurakarta Seri Topeng Bujang Ganong - Gladi Pawestri Utami (Jurnal Bahasa Rupa, 2021)
The purpose of this study is to find out meaning of the Bujang Ganong mask series mural by Youngsurakarta using Erwin Panofski's iconological theory and iconography approach in order to get a deeper meaning of the mural work. This research uses descriptive qualitative research method with collection data technique by deep interviewing Youngsurakarta. The purposive sampling is to do research of murals made by Youngsurakarta with the Bujang Ganong mask series. This research finds that the characters made by Youngsurakarta is the reflection from “Young Surakarta” name which has meaning young man from Surakarta who has expressive and brave characters, represented through characters inspired by Bujang Ganong mask as one of his work characteristics. Bujang Ganong is one of Reog performances which is always awaited by the audience because of its characteristics which are energetic and funny. It can be concluded that Youngsurakarta understands that mural is just not only aesthetics elements but it is more than that. Murals made by Youngsurakarta gives young optimism which is energetic, passionate spirit. In his mural works, Youngsurakarta always slips local cultural elements, responding social cultural issues in kampong local community.